The contentious relationship between feminist scholarship and university sexual violence policies: 1980-2021 - Roberts, Lily May (Rhodes University, Faculty of Humanities, Department of History)
This thesis tracks the historically contentious relationship between feminist scholarship and university sexual violence policies. It examines the rise of the managerial university in South Africa, and the overlapping development of sexual violence policies through feminist activism from the early 1990s. Through an examination of the sexual violence policies of the University of Cape Town, the University of the Witwatersrand, Rhodes University, Stellenbosch University, and the University of the Western Cape, this thesis argues that these policies are aimed at 'managing' the process of reporting, rather than dismantling the broader structures "“ both within the university and society as a whole "“ that lead to and enable sexual violence. In this way, sexual violence policies are governed by a managerial discourse, limiting the possibility of addressing the dismantling of structures and discourses that perpetuate sexual violence, which, as I argue, is fundamentally opposed to the intellectual and political project of feminist scholarship from which these sexual violence policies initially emerged. However, this thesis also argues that feminist scholarship is not immune to the influence of managerialism, as discourses of efficiency and effectiveness have shaped Gender and Women's Studies, where feminist scholarship is often located. I use the #RUReferenceList protests that drew on black feminist scholarship and came under managerial control as an example of the contentious relationship between managerialism and feminist activism.
Keywords: Sexual assault -- South Africa History; Women college students Crimes against -- South Africa; Feminism and higher education -- South Africa; Educational leadership -- South Africa; Education, Higher Administration